One‐pot Synthesis of Propargylamines using Aldehydes‐Amines‐Acetylene via an Efficient Nickel‐Based Silica‐Coated Magnetic Nanocatalyst. Issue 33 (5th September 2022) - Yadav, Priya; Gupta, Radhika; Arora, Gunjan; Srivastava, Anju; Sharma, Rakesh K.
Abstract: This work discloses the fabrication and characterization of a highly efficient and magnetically retrievable nickel‐based silica‐coated nanocatalyst that has been utilized to obtain relatively large number of biologically significant propargylamines via one pot fashion. A facile co‐precipitation approach was employed for obtaining spherical and disperse Fe3 O4 nanoparticles, which were further modified using suitable protecting and functionalizing agents. The successful formation of nanocatalyst was thoroughly investigated by various physio‐chemical techniques such as FT‐IR, SEM, TEM, XRD, VSM, XPS, ICP‐MS and ED‐XRF The present strategy offered greener reaction condition, broad substrate scope, short reaction time and reusability up to seven runs without any appreciable loss in its catalytic activity. Moreover, it is noteworthy that this atom economical methodology does not require any co‐catalyst or activator. Hence, the outcomes of the present methodology prove the nanocatalyst is a suitable candidate for the development of green and sustainable chemical processes. Abstract : Highly proficient nickel‐based magnetically retrievable nanocatalyst was synthesized, characterized and further utilized for A 3 coupling of aldehydes‐amines‐acetylene for the one pot synthesis of propargylamines